Finite Element Analysis of Acrylic Denture Produced from Metal Stock Tray - Nadira A Hatim; Ayad A Abdul-Razaq; Ibtehal H Al-Zubaidy (Al-Rafidain Dental Journal, 2009)
Aims: To determine stress analysis exerted by denture on the edentulous alveolar bone in the premolarregion represented by stone cast produced from metal stock tray using linear finite element method.Materials and methods: Metal perforated stock tray was used to produce stone cast that represent thedenture base and the underlying bone using silicone impression material. The dimension of the crosssection of the stone cast was measured using Dimax program, then the data collected was entering Excelprogram for making the figures. The dimension of the cross section of the stone cast entering finiteelement program and other new auxiliary program prepared specially for this study for finite elementanalysis. Results: After the data was analyzed, the results were drawn in figures using surfer 7 program.High compressive, tensile, deflection, shear and maximum principal stress values were observedbelow the point of force application and in the underlying structure with different values and locationsaccording to the analysis in the mucous membrane and in the underlying bone in the X and Y axes.Conclusions: By using finite element analysis, the more stress concentration and deflection were foundbelow the point of force application, in the mucous membrane, at the beginning of the cortical bone andalong the buccal vestibule.